Sistem Informasi Persediaan Barang dengan Metode Perpetual pada Toko Mebel Sidarta Berbasis Web - Rizqi Saputra; Sri Sumarlinda; Wijiyanto Wijiyanto (Sekawan Institut, 2024)
Inventory of goods is an important component in company operations, especially for companies that sell finished goods such as furniture and household electronics. The aim of this research project is to create a goods management website using the Perpetual method at the Sidarta Furniture Store. Previously, this shop used manual recording through physical bookkeeping which was considered inefficient, prone to errors, and could hinder sales. To optimize inventory management, an in-tegrated system is needed. This system development uses the waterfall method, which consists of five stages, namely needs analysis, design, implementation, testing and maintenance. During the requirements analysis step, functional and non-functional system requirements are defined. System design involves developing use case diagrams, database design, and user interface design. The system is implemented using PHP as a programming language, CodeIgniter as a framework, and MySQL for database management. The black box testing method is used to carry out the system testing process, which ensures that all functionality operates according to predetermined speci-fications. The results of the tests carried out show that all system functionality functions in ac-cordance with the designed specifications. System maintenance, which is the final stage of the development cycle, is carried out periodically for the long-term sustainability of system opera-tions. This developed system allows the Sidarta Furniture Store to manage inventory data more efficiently and effectively by utilizing the perpetual method. This system is equipped with various features, including an inventory data management interface, supplier data management interface, purchase transaction recording interface, sales transaction recording interface, and the ability to produce comprehensive inventory recapitulation reports. Implementation of this system facili-tates the process of managing and updating inventory data more efficiently and accurately.